Knowledge and attitude towards childhood immunization among parents of paediatric patients at Hospital Universiti Sains Malaysia - Phian, Suniesa (2020)
Childhood immunization is one of the government strategies in reducing children mortality rates. However, there are still existence of unvaccinated children in Malaysia due to refusal of many parents. Parents’ knowledge and attitude towards immunization are likely influence uptake of vaccination. The aim of this study was to determine the level of knowledge and attitude towards childhood immunization among parents in Hospital USM. A cross-sectional study was conducted in paediatric wards in Hospital USM. A total of 150 respondents was recruited through systematic random sampling method and data was collected using a structured self-administered questionnaire. Majority of the respondents were female (94%) aged between 21 to 35 years old, Malay (92.7%), parents with secondary school (64%) and having household income RM1001 to RM5000 (74%). Results showed that 65.3% of the respondents had adequate knowledge regarding childhood immunization. However, there were 34.7% of the respondents had inadequate knowledge towards childhood immunization. Furthermore, 93.3% had positive attitude towards childhood immunization, while only 6.7% had negative attitude on immunization. Pearson Chi-square test was used to determine the association between selected socio-demographic characteristics and level of knowledge and attitude. This study showed that age (p=0.148), gender (p=0.065), ethnicity (p=0.651), and number of children (p=0.161) were not significant association with knowledge. However, the study found that educational level (p=0.010) and household income (p=0.049) were significant association with level of knowledge on childhood immunization. Furthermore, this study also revealed that age (p=0.818), gender (p=0.122), ethnicity (p=0.229), number of children (p=0.909) and educational level (p=1.000) were not significant association with attitude level. Meanwhile, the study found that there was significant association between household income and level of attitude towards childhood immunization (p=0.011). In conclusion, the study showed that parents had an adequate knowledge and positive attitude towards childhood immunization. However, educational programs are still needed to increase knowledge and attitude among parents and improve the immunization rate.